Networks to Strengthen Health Systems for Chronic Disease Prevention - Willis, Cameron D. (American Public Health Association, 2013)
Interorganizational networks that harness the priorities, capacities, and skills of various agencies and individuals have emerged as useful approaches for strengthening preventive services in public health systems. We use examples from the Canadian Heart Health Initiative and Alberta’s Primary Care Networks to illustrate characteristics of networks, describe the limitations of existing frameworks for assessing the performance of prevention-oriented networks, and propose a research agenda for guiding future efforts to improve the performance of these initiatives. Prevention-specific assessment strategies that capture relevant aspects of network performance need to be identified, and feedback mechanisms are needed that make better use of these data to drive change in network activities.